Learning of Status of Physical Properties of Peat in Palm Oil, Areca and Coffee in Mekar Jaya Village - Nasution, Hasriati; Saat, Asmadi; Yusfaneti, Yusfaneti (Attractive : Innovative Education Journal, 2022)
The aim of the research was to see the differences caused by planting oil palm, areca nut, coffee and forest plantations. While the benefits to be achieved are to be able to make preventive recommendations so that the properties of peat soil will always be stable and peat soil can be used sustainably. The research was conducted in a field survey using Proportional Random Sampling Method on oil palm, areca nut, coffee and secondary forest soils. Samples were taken from each plant as many as 20 samples. Data were analyzed on land planted with oil palm, areca nut, coffee and forest soil. To see the differences in the physical properties of the soil, peat thickness, peat water level, organic matter content, c-organic content, r volume weight, water content in the Unpaired Median Value Test at the 5% level (Steel and Torrie, 1995). From the research results, the unpaired mean test results for oil palm, areca nut, coffee and forest soil were obtained at the depth of peat soil on oil palm plantations, which was significantly different from the depth of peat soil on areca palm, coffee plantations and with coffee plantation soil and forest soil. The organic matter content for pinnag and forest plants is the same, but significantly different for oil palm and coffee plants. Meanwhile, C-oganic levels differed between oil palm, areca nut, coffee and forest plants. The volume weight is significantly different from the volume weight in areca palm, coffee and forest plantations. The soil water content in oil palm plants has the same water content as coffee and is significantly different from that of areca nut and forest plants. The conclusion is that the physical properties of the soil on coffee plants are almost the same as forest soil. Keywords: Physical Properties, Status Physical Properties, Planting